Antibacterial Properties of Gemifloxacin and Trovafloxacin in Urine Ex Vivo: Phase I Study - García-Calvo, Gloria (American Society for Microbiology, 2001)
Urine bactericidal titers (UBTs) against Escherichia coli ATCC 25922 and Staphylococcus saprophyticus ATCC 1970 were determined after the administration of single oral doses of gemifloxacin at 320 mg and trovafloxacin at 200 mg to healthy volunteers. Gemifloxacin presented significantly lower experimental versus mathematically predicted UBTs over 72 h, due to the effect of urine on the susceptibility of the E. coli strain. Experimental UBTs were significantly higher for gemifloxacin than trovafloxacin against both strains over 72 h.